Practical Training Report Institut Kemahiran MARA (IKM) Kuching / Wan Noor Azreen Wan Mohamad Nordin - Wan Mohamad Nordin, Wan Noor Azreen (University Technology MARA Sarawak, 2014)
Institut Kemahiran MARA (IKM) is an educational institution run by the agencies established under the Majlis Amanah Rakyat (MARA). IKM Kuching is one of the oldest ofthe Institute of Technical Education in Sarawak. This institute was established in 1983 and has been built on an area of 18.81 hectares. Began operations with a total intake of 51 person in 1984 with four skills course offered: Course of Works Pipe, Course of Brick and Plastering Embedding, Course of Carpentry and Joinery, and Course of Furniture and Craft. The next three courses was added which are Course ofKajisawat Motor in 1988 but has been stopped in 1993, Course of Gas and Arc Welding and Course of Electrical of Domestic and Industry. In 1990, the Course ofKnock and Painting Vehicle has been introduced. Institut Kemahiran MARA (IKM) Kuching are step forward when adding several courses like Course Technology of Maritime (1998), Course Technology of Automotive and Course Technology ofElectrical (Power).